Standardization in ethanolic extract of Paronema canescens leaves - Dirli Fahmi Rizal; Muharni Muharni; Heni Yohandini; Ferlinahayati Ferlinahayati (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
The development of traditional medicinal plants as raw materials for herbal drugs needs to be standardized. The aim of the research was to standardise ethanol extract of Paronema. canescens leaves.  The extract was determined specific and non-specific parameters. The organoleptic of  extract has a thick consistency, the colour dark brown has a characteristic non-aromatic odour, and has a slightly bitter taste. The soluble content in water and ethanol of 48.1% and 80. 3%, respectively. The extract contains triterpenoid compounds, steroids, flavonoids and phenols with water content was 8.33%, total ash content of 5.36%,  acid insoluble ash content of 2.16%,  drying shrinkage of 8.0%,  specific gravity of 1.255 g/ml, metal contamination Pb < 0.0628 mg/g, Cd 0.0077 mg/Kg and Cu 0.00282 mg/g, total bacterial  of 0.9 x 101 colonies/g and mould contamination with a value of 0.15 x 101 colonies/g, respectively. Based on the data, all the parameters were measured to meet the standardKeywords: Paronema canescens, standardised, specific parameter, non specific parameter